Răspuns:
5[tex]\sqrt{2}[/tex] + 3[tex]\sqrt{3}[/tex] - 3[tex]\sqrt{6}[/tex]
5[tex]\sqrt{2}[/tex] + 3[tex]\sqrt{6}[/tex] × ([tex]\frac{3\sqrt{2} }{2}[/tex] - [tex]\frac{5}{5}[/tex]) - 6[tex]\sqrt{3}[/tex] = 5[tex]\sqrt{2}[/tex] + 3[tex]\sqrt{6}[/tex] × ([tex]\frac{3\sqrt{2} }{2} - 1[/tex]) - 6[tex]\sqrt{3}[/tex] = 5[tex]\sqrt{2}[/tex] + [tex]\frac{9\sqrt{12} }{2}[/tex] - 3[tex]\sqrt{6}[/tex] - 6[tex]\sqrt{3}[/tex] = 5[tex]\sqrt{2}[/tex] + [tex]\frac{18\sqrt{3} }{2}[/tex] - 3[tex]\sqrt{6}[/tex] - 6[tex]\sqrt{3}[/tex] = 5[tex]\sqrt{2}[/tex] + 9[tex]\sqrt{3}[/tex] - 3[tex]\sqrt{6}[/tex] - 6[tex]\sqrt{3}[/tex] = 5[tex]\sqrt{2}[/tex] + 3[tex]\sqrt{3}[/tex] - 3[tex]\sqrt{6}[/tex]